Social work training to reduce duration of untreated psychosis: Methodology and considerations of a web‐based training for community providers. Issue 4 (24th May 2021) - Andorko, Nicole D.; Fitzgerald, John; Roemer, Caroline; Solender, Eric; Petti, Emily; Rakhshan Rouhakhtar, Pamela; McNamara, Karen E.; Smith, Melissa E.; Buchanan, Robert W.; Schiffman, Jason; DeVylder, Jordan
Abstract: Aim: Outcomes for individuals with psychotic disorders can be improved through early intervention services; however, identification continues to be a major problem in connecting individuals with these services. Social workers form a vast majority of the human service and mental health workforce in the United States and therefore have the potential to play a unique role in identifying and referring those who may benefit from specialty early intervention services. Methods: The current article describes the methodological design, implementation, and participant recruitment procedures of a large‐scale, web‐based training program for social workers promoting identification and referral of individuals with emerging symptoms of a mental illness with psychosis in the context of a randomized clinical trial. Results: The web‐based study enrolled 1384 individuals. More than half of study participants enrolled within the first 3 months of the 14‐month recruitment period. Completion of all study components was achieved by 959 individuals (69% of total enrolled), and completion status did not vary significantly by gender, ethnicity, or facility at which the individual was employed. Completion rates varied by race, such that participants identifying as White were more likely to complete the study, while those identifying as Black were less likely. Discussion: The results suggest the feasibility of using a web‐based training program to engage social workers in early psychosis identification practices. Challenges related to encouraging participants to complete the training and lessons learned during the study recruitment are discussed.